Roles of different polysaccharides on the structures of alginate-based Bigel beads and co-delivery of bioactives - Guangmin Liu; Yuxuan Wang; Jingyi Yang; Yaqin Wang; Hongju He; Like Mao (Food Chemistry: X)
Bigels are novel soft-solid materials, which attract increasing attentions in the food industry. In this study, bigel beads based on alginate hydrogel and monoglyceride oleogel were developed, and their structures were modified by adding various polysaccharides (pectin, carrageenan, chitosan, xanthan gum and konjac gum). The inclusion of polysaccharides generally increased bead size and decreased hardness, with chitosan reducing the shrinking rate and swelling ratio during simulated gastric-intestinal digestion. FTIR analysis confirmed no interactions between alginate hydrogel and monoglyceride oleogel, nor covalent bonds formation between alginate and the polysaccharides. The bigels were tested for simultaneously delivery of epigallocatechin gallate and curcumin, and the results showed that bead structures significantly influenced their release. Among all tested bigels, pectin and carrageenan beads exhibited the highest cumulative release in simulated intestinal fluid. The results suggested that polysaccharides effectively modified the physicochemical properties of alginate-based bigel beads, leading to adjustable release of the incorporated bioactives.